08.60: Composite dowels in cracked concrete Experimental investigation. (13th September 2017) - Classen, Martin; Christou, Georgios; Hegger, Josef
ABSTRACT: In steel‐concrete composite girders, composite dowel shear connectors can be used to transfer shear forces between the concrete slab and the steel section. In comparison to other shear connectors the composite dowels offer increased strength capabilities, higher deformation capacities both in normal and in high strength concrete and offer an efficient use of steel and concrete. Composite dowels gain increasingly acceptance and are more and more used especially for prefabricated constructions. In regions with negative bending moment – for example near the interior supports of continuous composite beams, where concrete cracking occurs, the shear capacity of composite dowels may be affected by transverse concrete cracks. So far, the internal shear carrying mechanisms of composite dowels in cracked concrete are not clarified and existing shear capacity models do not account for concrete cracking. Hence, the present paper summarizes the results of 38 shear tests, providing novel insights regarding the pry‐out failure of composite dowels in cracked concrete. The tests were performed in an innovative test setup, whereby concrete was cracked prior to the test allowing to investigate the impact of crack spacing and crack width.